Structural Characterization of Ijero – Ekiti, Ekiti State, Nigeria Kaolin for Use as Refractory Material (2016)
This work investigates the structural properties of a selected kaolin deposit in Ijero – Ekiti, Nigeria. Some processed quantity of the clay was collected and prepared for laboratory analyses. Sieve and X-ray Diffraction analyses were carried out on the clay sample whilst still in the as – received state, using the electric sieve and X-ray Mini Diffractometer respectively for the tests. Sieve analysis results showed that the Ijero – Ekiti kaolin is fine textured. X-ray analysis showed kaolinite which melts at 1700OC when pure to be prominent in the clay type. In conclusion, the clay type from the Ijero – Ekiti kaolin deposit, with its high content of kaolinite, is highly refractory in nature, and so will adequately serve as a refractory material suitable for foundry uses. This study has significance in sourcing for quality refractory materials for the development of foundries for metallurgical purposes. In essence, Ijero-Ekiti Kaolin from Ekiti State, Nigeria can be classified as a refractory material useful in meeting foundry demands.